The immunoregulatory effect of the TREM2-agonist Sulfavant A in human allogeneic mixed lymphocyte reaction - Barra, Giusi; Gallo, Carmela; Carbone, Dalila; Ziaco, Marcello; Dell’Isola, Mario; Affuso, Mario; Manzo, Emiliano; Nuzzo, Genoveffa; Fioretto, Laura; D’Ippolito, Giuliana; De Palma, Raffaele; Fontana, Angelo (Frontiers in Immunology, 2023)
Sulfavant A (SULF A) is a synthetic derivative of natural sulfolipids that induces dendritic cell (DC) maturation and shows promising adjuvant activity in a cancer vaccine model. In this work, we analyzed the in vitro effect of SULF A in an inflammatory model of allogeneic mixed lymphocyte reaction (MLR) with monocyte-derived dendritic cells (MoDCs) and naïve T lymphocytes of different donors over 7 days. The addition of SULF A to the cocultures induced the exposure on MoDCs of costimulatory molecules ICOS-L and OX40L mainly involved in immunoregulation and the reduction of the pro-inflammatory cytokine IL-12. T lymphocytes exhibited more robust proliferation of the TCD4+ subset compared to untreated MLR and increased production of the anti-inflammatory cytokine IL-4 associated with the down-regulation of the Th1 cell markers T-BET, CXCR3, and IFNγ. SULF A also promoted the polarization of naïve T cells toward a regulatory phenotype showing up-regulation of FoxP3 expression and IL-10 release. Flow cytometry analysis revealed priming of a CD127-/CD4+/CD25+ Treg subpopulation was also positive for the inhibitory molecule CTLA-4, the activation marker CD69, and the costimulatory molecule ICOS that binds ICOS-L expressed on mature DCs. These results corroborate the previous evidence on the unconventional immunomodulatory activity of SULF A that first promotes DC-activated T cell response and later triggers immune tolerance and the restoration of homeostasis.